The Role of the Population, Family Planning and Family Development Program (KKBPK) in Reducing Stunting Prevalence - Agus Mauluddin; Novianti Novianti (CIC Lembaga Riset dan Konsultan Sosial, 2020)
Stunting is a common issue in the global network. Stunting is one of the fundamental problems that hinder the development of toddlers in the world today and has received great international attention, at least in the last decade. In 2017, for example, around 150.8 million (22.2%) children in the world were stunted. The stunting prevalence data collected by WHO (2005-2017) puts Indonesia in third position, the country with the highest prevalence in the Southeast Asia region (36.4%). Basic health research data in 2018 shows the prevalence of stunting in Indonesia is around 30.8% and is still below the world standard (WHO), which is a maximum of 20%. Many interventions have been carried out to reduce the prevalence of stunting, especially from a (specific) health aspect. However, interventions that only target specific interventions are still ineffective, hence the need for interventions that involve various sectors or stakeholders. The argument from this study is the need for stunting prevention interventions that involve multi-sectors, not only specific ones (health), but also sensitive interventions (Population, Family Planning, and Family Development programs). Strengthened by the latest research shows the focus of studies on multi-sector stunting prevention. Recent studies also prove that it is important to pay attention to a family-based approach (family development) in the prevention of stunting, especially in regards to birth interval management which has an effect on reducing the prevalence of stunting.